State-of-the-art hydrogen generation techniques and storage methods: A critical review. (1st August 2023) - Tang, Dan; Tan, Guang-Lei; Li, Guo-Wei; Liang, Jin-Guang; Ahmad, Shah Masood; Bahadur, Ayesha; Humayun, Muhammad; Ullah, Habib; Khan, Abbas; Bououdina, M.
Abstract: Hydrogen is a clean, versatile, and energy-dense fuel that has the potential to play a key role in a low-carbon energy future. However, realizing this potential requires the development of efficient and cost-effective hydrogen generation and storage technologies. Hydrogen can be generated from a variety of sources, including fossil fuels, biomass, and renewable energy sources such as solar and wind. In regard to the renewable energy sources, this paper presents a review of the state-of-the-art in hydrogen generation methods including water electrolysis, gasification, dark fermentation, steam reforming, photocatalytic water splitting and water thermolysis. Further, this paper presents a review of the various hydrogen storage methods, including compression, liquefaction, liquid organic carriers, and solid-state storage. These technologies offer the potential for improved efficiency, safety, and environmental performance, and may play a key role in the transition to a hydrogen-based energy system. Finally, the advantages and challenges of hydrogen energy, and future perspectives on the improvement of hydrogen storage methods are well emphasized. Overall, the development of efficient and cost-effective hydrogen generation and storage technologies is essential for the widespread adoption of hydrogen as a clean energy source. Continued research and development in this field will be critical to advancing the state-of-the-art and realizing the full potential of hydrogen as a key element in a sustainable energy future. Graphical abstract: Unlabelled Image